Provision of emergency contraception in general practice and confidentiality for the under 16's: Results of a postal survey by general practitioners in Avon. Issue 4 (1st October 2001) - Graham, Anna; Moore, Laurence; Sharp, Deborah
Abstract : Objective: To describe the provision of emergency contraception and confidentiality for the under 16's by general practitioners (GPs) in Avon, in order to inform the development of a health promotion intervention in schools in Avon. Design: Confidential postal questionnaire survey. Setting: All principals in general practice in Avon Health Authority, South West England. Subjects: Five hundred and eighty general practice principals were sent the questionnaire. Results: Four hundred and eighty-six (84%) principals in general practice responded to the questionnaire. Only three (0.6%) GPs did not provide hormonal emergency contraception. Nearly half (232, 47.7%) would fit the intrauterine device (IUD) as emergency contraception. Fitting an IUD was associated with female gender of the GP (OR = 2.34, 95% CI 1.53-3.71), and whether the GP had a family planning qualification (OR = 4.55, 95% CI 2.41-8.60). Three hundred and fifty-two (72%) respondents would provide emergency contraception on a Sunday if requested to do so by a 14-year-old who reported having had unprotected sex the night before. Practice nurses in 26 (5%) of the respondent's practices were available to provide advice and tablets for patients requesting hormonal emergency contraception. However, 74 (21%) respondents employed a family planning trained practice nurse who was not involved in any way in the provision of emergency contraception. Practice nurses remain an under used resource in this area. Conclusion: Our findings suggest that most GPs provide hormonal emergency contraception. Only eight (1.6%) of respondents would need to ask for parental consent prior to providing hormonal emergency contraception to a 14-year old-girl. Young people need to be informed of GPs widespread adherence to current confidentiality guidelines.